2016
DOI: 10.1038/srep20493
|View full text |Cite
|
Sign up to set email alerts
|

Novel Osteogenic Ti-6Al-4V Device For Restoration Of Dental Function In Patients With Large Bone Deficiencies: Design, Development And Implementation

Abstract: Custom devices supporting bone regeneration and implant placement are needed for edentulous patients with large mandibular deficiencies where endosteal implantation is not possible. We developed a novel subperiosteal titanium-aluminum-vanadium bone onlay device produced by additive manufacturing (AM) and post-fabrication osteogenic micro-/nano-scale surface texture modification. Human osteoblasts produced osteogenic and angiogenic factors when grown on laser-sintered nano-/micro-textured surfaces compared to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
86
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 34 publications
1
86
0
4
Order By: Relevance
“…Previous studies have shown differences in bone healing around hydroxyapatite implants placed in rabbits up to 6 months after implantation [26]. Work from our group has also shown varied response to additively manufactured implants at 5 weeks compared to 10 weeks [13]. It may be possible that differences in healing occurred at an earlier time point, but stabilized for both implants after 10 weeks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown differences in bone healing around hydroxyapatite implants placed in rabbits up to 6 months after implantation [26]. Work from our group has also shown varied response to additively manufactured implants at 5 weeks compared to 10 weeks [13]. It may be possible that differences in healing occurred at an earlier time point, but stabilized for both implants after 10 weeks.…”
Section: Discussionmentioning
confidence: 92%
“…This model is also more relevant than the calvarial bone onlay model, providing the ability to evaluate response to an implant size that could be used clinically. While vertical cortical bone formation had been previously observed in the cranial bone onlay model in rats, it was unclear how osseointegration would occur horizontally within trabecular bone [13]. For orthopaedic implants and for dental implant placement in the mandible, the ratio of cortical to cancellous bone contributes to primary stability and long term success [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of elderly patients with very pronounced bone atrophy, the placement of endosseous implants via bone regenerative techniques may be unwise [13, 4244]. Such patients may have general (medical) health problems, or may simply not want to pursue a treatment option involving multiple invasive procedures (e.g., hip grafting), the risk of complications and postoperative pain, and increased cost and time of treatment, simply to gain stability and increase masticatory function to that of a complete removable denture [10, 13, 15, 16, 4244].…”
Section: Discussionmentioning
confidence: 99%
“…DMLS is an additive manufacturing (AM) method for creating patterns using thermal fusing (sintering) of powdered metals [4044, 48]. DMLS models are generated directly from 3D computer data converted to STL files, which are then sliced into thin layers (typically about 0.1 mm/0.004 inches) using appropriate software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation